EFFORTS OF THE COMMUNITY IN INCREASING TOURIST VISITS TO THE PADANG ROCO TEMPLE TOURISM OBJECT IN DHARMASRAYA REGENCY - Melinia, Indah; Sarbaitinil, Sarbaitinil; Rahmadani, Sri (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The tourism sector will become a national asset if it can be well-developed. One of the ways is by promoting tourist attractions, which is not only the responsibility of the government but also the community. The community plays a vital role in developing and maintaining the values of a tourist object. Hence, this research aims to examine the community's efforts in increasing tourist visits to the Padang Roco Temple Tourism Object in Dharmasraya Regency. The research approach used in this study was qualitative with a descriptive research type, and 12 informants were selected through purposive sampling. Data collection techniques included observation, interviews, and document studies. The analysis technique used was the Miles and Huberman model, which includes data collection, reduction, presentation, and conclusion. Based on the research results, the government and the community have tried to develop the Padang Roco Temple Tourism Object. Some of the efforts include 1) efforts by the caretakers of the temple to develop the facilities and infrastructure, 2) efforts by the local community groups to promote the Padang Roco Temple Tourism Object, and 3) efforts by the community to help in the development of the temple by donating land to the government.